Evaluating symptoms of chronic rhino sinusitis and most common sinuses affected - Jaafar Khalaf , Qays (Diyala Journal of Medicine, 2023)
Background: Chronic rhinosinusitis is a common condition that significantly affect the quality of life, high health-care consumption and significant comorbidity. Objective: To investigate and identify the symptoms that are most often experienced by people with chronic rhinosinusitis. Patients and Methods: In this cross-sectional study, we conducted one hundred patients complaining of chronic rhinosinusitis presented to the outpatient clinic for otolaryngology at Baquba teaching hospital; the patients were chosen randomly. A careful clinical examination following comprehensive history taking done for all of the patients. All patient's main complaint were nasal airway obstruction, nasal discharge, and anosmia. In addition to a clinical evaluation, a computed tomography (CT) scan of the nose and paranasal sinuses was performed,. And Diagnostic nasal endoscopy Results: The population under investigation had a mean age of 35 years and was mostly comprised of males. The majority of patients in this study reported a common symptoms, including nasal congestion (72%), headache (68%), and rhinorrhea (mucus discharge) (58%) Conclusion: Chronic rhinosinusitis is characterised by a set of symptoms that, if caught early, may be diagnosed and treated effectively.